The Aging Auditory System - Gordon-Salant, Sandra; Frisina, Robert D.; Popper, Arthur N.; Fay, Richard R.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
This volume is to bring together noted scientists who study presbycusis from the perspective of complementary disciplines, for a review of the current state of knowledge on the aging auditory system. Age-related hearing loss (ARHL) is one of the top three most common chronic health conditions affecting individuals aged 65 years and older. The high prevalence of age-related hearing loss compels audiologists, otolaryngologists, and auditory neuroscientists alike to understand the neural, genetic and molecular mechanisms underlying this disorder. A comprehensive understanding of these factors is needed so that effective prevention, intervention, and rehabilitative strategies can be developed to ameliorate the myriad of behavioral manifestations. The aim is to provide students and researchers in auditory science and aging with a understanding of the various effects of aging on the auditory system. Contents: Introduction and Overview Sandra Gordon-Salant and Robert D. Frisina The Physiology of Cochlear Presbyacusis Richard A. Schmiedt The Cell Biology and Physiology of the Aging Central Auditory Pathway Barbara Canlon, Robert Benjamin Illing, and Joseph Walton Closing the Gap between Neurobiology and Human Presbycusis: Behavioral and Evoked Potential Studies of Age-related Hearing Loss in Animal Models and in Humans James R. Ison, Kelly L. Tremblay, and Paul D. Allen Behavioral Studies with Aging Humans: Hearing Sensitivity and Psychoacoustics Peter J. Fitzgibbons and Sandra Gordon-Salant. Binaural Processing and Auditory Asymmetries David A. Eddins and Joseph W. Hall III The Effects of Senescent Changes in Audition and Cognition on Spoken Language Comprehension Bruce A. Schneider, Kathy Pichora-Fuller, and Meredyth Daneman Factors Affecting Speech Understanding in Older Adults Larry E. Humes and Judy R. Dubno Epidemiology of Age-related Hearing Impairment Karen J. Cruickshanks, Weihai Zhan, and Wenjun Zhong Interventions and Future Therapies: Lessons from Animal Models James F. Willott and Jochen Schacht Sandra Gordon-Salant is Professor and Director of the Doctoral Program in Clinical Audiology in the Department of Hearing and Speech Sciences at the University of Maryland, College Park. Robert D. Frisina is Professor of Otolaryngology, Neurobiology & Anatomy, and Biomedical Engineering, and Associate Chair of Otolaryngology at the University of Rochester Medical School. Arthur N. Popper is Professor in the Department of Biology and Co-Director of the Center for Comparative and Evolutionary Biology of Hearing at the University of Maryland, College Park. Richard R. Fay is Director of the Parmly Hearing Institute and Professor of Psychology at Loyola University of Chicago. About the series: The Springer Handbook of Auditory Research presents a series of synthetic reviews of fundamental topics dealing with auditory systems. Each volume is independent and authoritative; taken as a set, this series is the definitive resource in the field.
and Overview -- The Physiology of Cochlear Presbycusis -- Cell Biology and Physiology of the Aging Central Auditory Pathway -- Closing the Gap Between Neurobiology and Human Presbycusis: Behavioral and Evoked Potential Studies of Age-Related Hearing Loss in Animal Models and in Humans -- Behavioral Studies With Aging Humans: Hearing Sensitivity and Psychoacoustics -- Binaural Processing and Auditory Asymmetries -- Effects of Senescent Changes in Audition and Cognition on Spoken Language Comprehension -- Factors Affecting Speech Understanding in Older Adults -- Epidemiology of Age-Related Hearing Impairment -- Interventions and Future Therapies: Lessons from Animal Models.
Keywords: Medicine; Human physiology; Neurosciences; Geriatrics; Neurology; Otorhinolaryngology; Medicine & Public Health; Otorhinolaryngology; Neurosciences; Human Physiology; Geriatrics/Gerontology.; Neurology